기초생활권 계획 수립 관련 테마별 네트워크 포럼 컨설팅 보고서 - 김정섭 (한국농촌경제연구원, 2009)
One of three dimensional frameworks of regional development policies of the current government, ‘Basic Settlement Areas’ program necessitates each of 163 basic settlement areas to draw up its own development plan. One or two basic settlement areas can draft a development plan that suits local characteristics and potential and that will improve upon quality of life for local residents. The Korea Rural Economic Institute prepared a guidebook containing directives and principles useful for plan-making. Especially the Institute consulted and monitored the plan-making process in three types of case study areas, Yeoncheon, Jecheon-Danyang-Yeongwol, and Geochang-Sanchong-Hamyang, so that it can help to prepare a relevant and pertinent guidebook. These three case study areas purportedly represent urban (Type A), urban-rural linkage (Type B) and rural and fishing village (Type C) types respectively. In this process, the Institute provided a model or program, and policy suggestions, for cooperative roles among major actors of basic settlement areas, the central government and experts in the field. This report contains the consulting process and results on several issues of planning the 'Development Plan in Basic Settlement Areas'?(i) position and meaning of 'Development Plan in Basic Settlement Areas', (ii) scope of the plan , (iii) representation of cooperative planning among different Basic Settlement Areas, (iv) sectoral plans.